Developing counsellor training - Dryden, Windy; Feltham, Colin (London ; Thousand Oaks : Sage, 1994)
Assessing how counselling may be analyzed, systematized, reconsidered and improved, this book provides practical guidelines for trainers, those wishing to enter this field and others involved in the planning, implementation and evaluation of counsellor training programmes
Includes bibliographical references and index.
Keywords: Counseling psychology -- Study and teaching; Counseling psychologists -- Training of